Avaliação no processo de ensino aprendizagem: um estudo nos anos iniciais do ensino fundamental na escola Santa Rita de Cássia em Muaná - MORAES, Nayza Oliveira (2019)
The present work entitled Evaluation in the teaching-learning process: a study in the early years of elementary school at Santa Rita de Cássia Muaná presents the following problem: What is the importance of evaluation in the early years of elementary school at Santa Rita de Cássia? It aimed to make a reflection on assessment, seeking to identify the evaluation methods used by teachers in the early years of elementary school. We know that assessment of learning is present in our schools as a mechanism used by teachers to monitor their students' performance throughout the teaching-learning period, so this work sought to reflect on authors who are reference in the subject as Luckesi (1997), (2005 ), Araújo (2009) among others. And to give direction to the research process, as a methodological procedure, it was used na ethnographic research, where it is based on field research, making use of participant observation, conversation and image capture and the field diary for possible translation and analysis. The research informants were: one teacher and two elementary school teachers I. Through the analysis of the data obtained from the ethnographic research carried out in the school, it was possible to conclude that the teachers practice a diagnostic and continuous evaluation, and make use of some evaluative resources. While in some ways helping to improve the learning of their students, although they still use the test as a threat and classification tool, it is possible to see in them an interest and concern with teaching and learning of their students.